Itinerario arquitectónico de los teatros del centro de la ciudad de Palmira. - López Jiménez, Luis Angel (Universidad Antonio Nariño, 2021)
This document was born in response to the current problem that the city of Palmira in the department of Valle del Cauca presents, due to changes in urban dynamics, which generated new needs that resulted in the appearance of new technologies and equipment, directly affecting the artistic movement and its theatrical buildings which were forced to create new marketing strategies so as not to go bankrupt and others had no choice but to close the establishments.